Design and validation of cable-driven hyper-redundant manipulator with a closed-loop puller-follower controller. (October 2021) - Zheng, Yang; Wu, Baibo; Chen, Yuyang; Zeng, Lingyun; Gu, Guoying; Zhu, Xiangyang; Xu, Kai
Abstract: A slim manipulator with redundant degrees of freedom can be of great use for inspection and maintenance in confined spaces. Cable-actuation is often preferred because of the possible proximal placement of the actuators. However, tension induced elongation and friction of the cables may substantially vary under different manipulator poses. It is then difficult to achieve high positioning accuracy under different loading conditions, even when such a manipulator went through careful motion calibration and actuation compensation. This paper hence proposes a 12-section cable-driven hyper-redundant manipulator with 24 degrees of freedom and closed-loop control. Customized magnetic angle sensors were integrated at each joint with a carefully designed sensor communication network to achieve rapid joint feedback. A novel puller-follower controller was proposed to properly actuate three cables for each universal joint that connects adjacent manipulator sections. The two joint angles of the universal joint and the cable tensions can be simultaneously controlled with the proposed puller-follower controller. The design overview, system descriptions, kinematics and experimental characterizations are reported in detail. After automatic straightening from arbitrary initial statuses, the proposed manipulator can achieve ±0.5° precision at each joint, even under a tip load up to 500 g.